2013
DOI: 10.1111/1471-0528.12399
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic organ prolapse after subtotal and total hysterectomy: a long‐term follow‐up of an open randomised controlled multicentre study

Abstract: Objective To analyse the development of pelvic organ prolapse (POP) after subtotal (SH) and total hysterectomy (TH) in the long-term, and to assess patient-reported symptoms regarding pelvic floor dysfunction (PFD).Design Long-term follow-up study of a randomised controlled multicentre study.Setting Seven hospitals and one private clinic in the south-east of Sweden.Population Of the 184 women who were eligible from the original trial, 151 (82%) responded to a postal questionnaire and 128 (70%) were clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 34 publications
2
32
1
Order By: Relevance
“…Contrarily, Persson et al [12] found more women with anterior POP after SAH than after TAH (not statistically significant). Thakar et al [11] did not divide POP into compartments.…”
Section: Commentmentioning
confidence: 89%
See 1 more Smart Citation
“…Contrarily, Persson et al [12] found more women with anterior POP after SAH than after TAH (not statistically significant). Thakar et al [11] did not divide POP into compartments.…”
Section: Commentmentioning
confidence: 89%
“…Regarding mode of hysterectomy several randomized clinical trials (RCTs) [10][11][12][13][14] have compared total abdominal hysterectomy (TAH) and subtotal abdominal hysterectomy (SAH) regarding POP and UI; none have found differences between SAH and TAH.…”
mentioning
confidence: 99%
“…We were pleased to learn that our paper 1 on the rate of subsequent surgery following endometrial ablation had been discussed at Drs Vo and Banerjee's Journal Club, and that its results will be used to help counsel women with heavy menstrual bleeding.…”
Section: Sirmentioning
confidence: 99%
“…Sir, I read with interest the article by Persson et al 1 comparing the incidence of pelvic organ prolapse following total versus subtotal hysterectomy.…”
Section: Sirmentioning
confidence: 99%
“…1,2 The interpretation of the number of randomised control trials (RCTs) comparing abdominal subtotal hysterectomy (SH) and total hysterectomy (TH) should be seen not only in terms of the absolute number of RCTs but also in light of the time period during which the methods have been used. Both SH and TH have been used for more than a century but the first RCT presenting data on surgical outcomes was published in 2002.…”
Section: Sirmentioning
confidence: 99%